Carbon nanotube-reinforced smart composites for sensing freezing temperature and deicing by self-heating. (29th May 2018) - Jang, Sung-Hwan; Park, Yong-Lae
Carbon nanotube-reinforced polymer composites were fabricated by high shear mixing. The microstructure and the electrical properties of the carbon nanotube–polymer composites were investigated by scanning electron microscopy and electrical resistance measurement. We found that the carbon nanotube composites showed high electrical conductivity (1.5 S m −1 ) at 7.0 wt% of carbon nanotubes, and the increase in thickness enhanced the electrical conductivity of the composites. The multifunctional properties of the carbon nanotube composites were also investigated for use in sensing the freezing temperature and also in deicing by self-heating. The results showed that the carbon nanotube–polymer composites had high temperature sensitivity in the freezing temperature range from −5 to 5 C and an excellent heating performance due to the Joule heating effect. The carbon nanotube composites are promising to be used as smart coating materials for deicing by self-heating as well as by detection of the freezing temperature.